CS2164 and Venetoclax Show Synergistic Antitumoral Activities in High Grade B-Cell Lymphomas With MYC and BCL2 Rearrangements - Yuan, Delin; Li, Genhong; Yu, Lian; Jiang, Yuelong; Shi, Yuanfei; Chen, Qiulin; Ma, Xiaomei; Pham, Lan V.; Young, Ken H.; Deng, Manman; Fang, Zhihong; Xu, Bing (Frontiers in Oncology, 2021)
High-grade B-cell lymphoma with concurrent MYC and BCL2 rearrangements (HGBL-DHL) is a rare, aggressive mature B-cell malignancy with a high likelihood of treatment failure following front-line immunochemotherapies. Patients with HGBL-DHL who develop a relapsed or refractory disease have little effective therapeutic strategies and show very poor clinical outcomes, thus calling for development of novel therapies for this specific patient population. In this study, we investigated the preclinical anti-lymphoma efficacies and potential mechanism of action of a novel treatment approach, combining the BCL2 inhibitor venetoclax with CS2164, a new orally active multitarget inhibitor, in HGBL-DHL models. This combination therapy exhibited a robust synergistic cytotoxicity against HGBL-DHL cells, evidenced by cooperatively inducing loss of cell viability and promoting cell apoptosis. Moreover, coadministration of CS2164 and venetoclax resulted in significant superior suppression of HGBL-DHL cell growth and remarkably abrogated tumor burden in a HGBL-DHL-xenografted mouse model. The synergistic lethality of CS2164 and venetoclax in HGBL-DHL cells was associated with induction of DNA damage and impairment of DNA repair ability. Of importance, the combined treatment almost abolished the expression of both BCL2 and MYC, two hallmark proteins of HGBL-DHL, and substantially blunted the activity of PI3K/AKT/mTOR signaling cascade. In addition, MCL1 and BCL-XL, two well-characterized contributors for venetoclax resistance, were significantly lessened in the presence of CS2164 and venetoclax, thus leading to the accumulation of proapoptotic proteins BAX and PUMA and then initiating the intrinsic apoptosis pathway. Taken together, these findings suggest that the regimen of CS2164 and venetoclax is highly effective to eliminate HGBL-DHL cells in the preclinical setting, warranting further clinical investigations of this regimen for the treatment of unfavorable HGBL-DHL patients.